Comprehensive utilization method of multi-metal ilmenite
By using mixed acid medium for coordination leaching and countercurrent extraction technology in ilmenite, the separation and purification of elements such as titanium, iron, chromium, aluminum and silicon have been successfully achieved, solving the problem of comprehensive utilization of multiple elements in the existing technology, and improving resource utilization efficiency and production efficiency.
Patent Information
- Application Number
- CN202411990598.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing technology is difficult to achieve the comprehensive utilization of various elements in ilmenite, mainly focusing on the extraction and utilization of titanium elements. There is a lack of effective methods for the comprehensive utilization of elements such as aluminum, silicon, vanadium and chromium.
The complexes of each element are separated and purified by the mixed acid medium by leaching elements such as titanium, iron, chromium, aluminum and silicon through countercurrent extraction and multi-stage washing process, and finally prepared into a product that meets market demand.
It realizes efficient separation and purification of various elements in ilmenite, improves the comprehensive utilization efficiency of resources, reduces production costs, and reduces environmental pollution.
Abstract
Description
Technical Field
[0001] The present application relates to the field of titanium chemical industry and metallurgical technology, and specifically to a comprehensive utilization method of multi-metal ilmenite. Background Art
[0002] There are many kinds of raw materials containing elements such as titanium, iron, chromium, aluminum and silicon, such as high-titanium slag, titanium concentrate, vanadium-titanium magnetite, slag and beneficiation tailings. The components of each element in these raw materials are different, and comprehensive utilization is difficult. For high-titanium slag, a process for producing titanium tetrachloride by chlorination method has been developed, which mainly utilizes the titanium element in the raw material. For high-grade ilmenite, titanium dioxide is produced by sulfuric acid method, and titanium and iron elements are produced into titanium dioxide and ferrous sulfate. Other elements such as aluminum, chromium and vanadium are stored in the form of waste slag. Ilmenite is used to prepare rutile titanium dioxide for use in chlorination method, such as the process for preparing artificial rutile by hydrochloric acid leaching of ilmenite (CN 117800389 A). CN 116287784 A discloses a method for microwave alkali roasting of titanium concentrate-ultrasonic sulfuric acid leaching of titanium, the main purpose of which is to increase the leaching rate of ferrotitanium elements, and does not involve the comprehensive utilization of multiple elements. CN 110453093 A has developed a method for selectively leaching titanium from titanium-containing slag. The silicon element in the titanium-containing slag is removed in advance and the titanium element is selectively and efficiently leached. The impurity types and contents in the leached titanium liquid are small, which is conducive to the subsequent removal of impurity elements in the titanium liquid. Wang Yu from the Patent Office of the State Intellectual Property Office discussed the utilization of titanium-containing blast furnace slag in the article "Titanium Recovery Technology and Patent Analysis of Titanium-Containing Blast Furnace Slag". The article points out that about 4 million tons of titanium-containing blast furnace slag are produced in China every year, and the current stockpile has exceeded 80 million tons. For the comprehensive utilization of this huge amount of resources, it is proposed that titanium extraction and preparation of TiO2 will still be the focus in the future. The mainstream process technology is selective leaching separation and titanium extraction and acid leaching and hydrolysis hydrometallurgical titanium extraction. The research direction is to improve the separation or acid leaching or hydrolysis process to improve the efficiency of titanium extraction, reduce acid consumption and reduce environmental pollution. CN 117865217 A discloses a method for preparing titanium dioxide using blast furnace slag as raw material and titanium-rich material, wherein blast furnace slag with a titanium dioxide content of about 20% is used to produce titanium dioxide with a content of about 90%. Due to the complex composition of minerals, it is difficult to separate elements. Therefore, the existing methods all emphasize the use of titanium in minerals and the comprehensive utilization of aluminum, silicon, vanadium and chromium. In view of this current situation and technical difficulties, the present invention proposes to coordinately leaching titanium, iron, chromium, aluminum and silicon in a mixed acid medium, separate and purify the complexes of each element through solvent extraction, and then prepare each element into a product that meets market demand, thereby achieving the purpose of comprehensive utilization of each element in the raw material. Summary of the invention
[0003] The purpose of the present application is to provide a method for comprehensive utilization of multi-metal ilmenite, so as to solve the technical problem that various elements in the prior art cannot be comprehensively utilized.
[0004] To achieve the above objectives, the present application provides a method for comprehensive utilization of multi-metal ilmenite, comprising the following steps:
[0005] Step 1: leaching the titanium-containing raw material with a mixed acid to obtain a leaching solution;
[0006] Step 2: dissolving the leachate in a mixed solution of an extractant and an organic solvent for countercurrent extraction, and countercurrently washing the obtained organic phase containing titanium, iron, chromium, aluminum and silicon with a mixed solution of titanium ions and hydrogen fluoride, and then countercurrently washing with a mixed solution of iron ions and hydrogen fluoride solution, and then countercurrently washing the organic phase with a hydrogen fluoride solution, and then countercurrently washing the organic phase with pure water, and finally washing the organic phase with sodium hydroxide or sodium carbonate.
[0007] Preferably, in step 1, the mixed acid is sulfuric acid and hydrochloric acid, or sulfuric acid and chlorides such as sodium chloride and magnesium chloride, or the mixed acid is sulfuric acid and HF, or sulfuric acid and fluorides such as sodium fluoride and ammonium fluoride. A binary mixed acid system; or a ternary mixed acid system such as sulfuric acid containing chlorine and fluoride ions.
[0008] Preferably, in step 1, the titanium-containing raw material is leached with a mixed acid at a liquid-solid ratio of 0.1-10 to 1 at 10-90° C.;
[0009] Preferably, in step 2, the substituents R1 and R2 in the extractant are saturated or unsaturated straight chain or branched alkyl substituents with a carbon number of 1-20; or saturated or unsaturated straight chain or branched alkyl substituted phenyl with a carbon number of 1-20; or primary or secondary amine groups substituted with saturated or unsaturated straight chain or branched alkyl groups with a carbon number of 1-20.
[0010] Preferably, in step 2, the organic solvent is dissolved in a saturated or unsaturated straight chain or branched alkane with a carbon number of 6-20; or a saturated or unsaturated straight chain or branched alkyl substituted benzene with a carbon number of 6-20; or an ether substituted with a saturated or unsaturated straight chain or branched alkyl with a carbon number of 6-20.
[0011] Preferably, in step 2, the concentration range of chlorine or fluorine ions is 0.1-12 mol / L, the concentration of iron or titanium ions is 0.1-60 g / L, and the washing ratio of the mixed solution is 0.1-25 to 1, and the washing temperature is 10-80°C.
[0012] Preferably, the concentration range of sodium hydroxide or sodium carbonate detergent is 0-12 mol / L, the washing phase ratio is 0.1-25 to 1, and the washing temperature is 10-80°C.
[0013] Therefore, the present application provides a method for comprehensive utilization of multi-metal ilmenite, which has the following beneficial effects: the present application adds a certain amount of solid minerals containing multiple elements such as titanium and iron to a mixed acid solution of a certain volume and a certain ligand for leaching. After leaching for a certain period of time, the filtrate is obtained by filtration. The filter residue can be discharged or returned to the leaching process for further leaching according to the leaching rate of each element. The leachate containing the complex of elements such as titanium, iron, silicon and aluminum is fully mixed and stratified with an organic solvent containing an extractant, and the complex can be selectively transferred from the leachate to the organic solvent, and then fractionated and washed to obtain solutions of single elements. After post-treatment, these solutions can be prepared into products that meet market demand. DETAILED DESCRIPTION
[0014] The technical solution of the present invention is further illustrated by the following examples.
[0015] Example 1
[0016] The titanium-containing raw material containing 63.44% titanium dioxide, 10.75% total iron, 0.26% sodium oxide, 3.13% magnesium oxide, 4.85% aluminum oxide, 8.96% silicon dioxide, 3.23% calcium oxide, 0.60% vanadium pentoxide, 1.24% chromium trioxide, and 1.52% manganese oxide was leached at 70°C for 100 minutes with a mixed solution of sulfuric acid and HF in a liquid-solid ratio of 6 to 1. The total acidity of concentrated sulfuric acid and hydrofluoric acid is 8 mol / L, and the ratio of the amount of sulfuric acid to hydrofluoric acid is 6 to 4. The leaching rate of titanium is 97.17%, the leaching rate of iron is 98.42%, the leaching rate of aluminum oxide is 96.91%, the leaching rate of vanadium pentoxide is 97.23%, the leaching rate of manganese oxide is greater than 99.9%, and the leaching rate of silicon is 89.32%. The leaching solution is used as raw material to separate elements such as titanium, iron, aluminum, and silicon.
[0017] The above-mentioned leaching solution uses C dissolved in dodecylbenzene. 10 H 21-CO-NH-OH was used for extraction, the volume concentration of the extractant was 30%, the extraction temperature was 45℃, and the ratio was 2.5:1; after 8 levels of countercurrent extraction, the extraction rates of titanium, iron, chromium, aluminum and silicon were 99.32%, 99.92%, 2.5%, 23.24% and 99.88% respectively. The obtained organic phase containing titanium, iron, chromium, aluminum and silicon is counter-washed for five stages with a solution having a titanium concentration of 50 g / L and a hydrochloric acid concentration of 6 mol / L at a ratio of 8:1, and the elution rate of chromium is 99.45%; then, it is counter-washed for six stages with a solution having an iron concentration of 42 g / L and a hydrochloric acid concentration of 6 mol / L, and the elution rate of aluminum is 99.27%; then, it is counter-washed for six stages with a 1 mol / L hydrochloric acid solution at a ratio of 2:1, and the elution rate of titanium is 99.15%; then, it is counter-washed for 15 stages with pure water at a ratio of 1:1, and the washing rate of iron reaches 99.36%; finally, the organic phase is washed with 1.0 mol / L sodium hydroxide at a ratio of 6:1, and the number of stages is 8, and the elution rate of silicon is 98.78%. Each washing solution is concentrated and crystallized to obtain a complex containing chloride or chlorine. The organic phase is washed with water and returned to the extraction for continued use.
[0018] Example 2
[0019] The titanium-containing raw material containing 66.20% titanium dioxide, 8.77% total iron, 0.27% sodium oxide, 3.22% magnesium oxide, 4.93% aluminum oxide, 9.16% silicon dioxide, 3.52% calcium oxide, 0.58% vanadium pentoxide, 0.96% chromium trioxide, and 1.48% manganese oxide was leached at 65°C for 120 minutes with a mixed solution of sulfuric acid and HF in a liquid-solid ratio of 5 to 1. The total acidity of concentrated sulfuric acid and hydrofluoric acid is 12 mol / L, and the ratio of the amount of sulfuric acid to hydrofluoric acid is 7 to 3. The leaching rate of titanium is 98.23%, the leaching rate of iron is 98.58%, the leaching rate of aluminum oxide is 97.25%, the leaching rate of vanadium pentoxide is 97.34%, the leaching rate of manganese oxide is greater than 99.9%, and the leaching rate of silicon is 92.43%. The leaching solution is used as raw material to separate elements such as titanium, iron, aluminum, and silicon.
[0020] The above leachate uses C8H dissolved in saturated hexadecane. 17 -CO-CO-NH-C8H 17The extraction was carried out with an extractant volume concentration of 45%, an extraction temperature of 50°C, and a ratio of 3:1; after 10 levels of countercurrent extraction, the extraction rates of elements such as titanium, iron, chromium, aluminum and silicon were 99.46%, 99.94%, 4.66%, 32.16% and 99.93% respectively. The obtained organic phase containing titanium, iron, chromium, aluminum and silicon is counter-currently washed for five stages with a solution having a titanium concentration of 40g / L and a hydrogen fluoride concentration of 1.5mol / L at a ratio of 15:1, and the elution rate of chromium is 99.83%; then, it is counter-currently washed for 7 stages with a solution having an iron concentration of 53g / L and a hydrogen fluoride concentration of 3mol / L, and the elution rate of aluminum is 99.43%; then, it is counter-currently washed for 8 stages with a 0.5mol / L hydrogen fluoride solution at a ratio of 3:1, and the elution rate of titanium is 99.75%; then, it is counter-currently washed for 8 stages with pure water at a ratio of 1:1, and the washing rate of iron reaches 99.44%; finally, the organic phase is washed with 1.0mol / L sodium hydroxide, at a ratio of 15:1, and the number of stages is 8, and the elution rate of silicon is 98.88%. Each washing solution is concentrated and crystallized to obtain a complex containing fluoride or fluorine. The organic phase is washed with water and returned to the extraction for continued use.
[0021] Example 3
[0022] The titanium-containing raw material containing 23.25% titanium dioxide, 8.01% magnesium oxide, 13.31% aluminum oxide, 25.05% silicon dioxide, 26.94% calcium oxide, and 0.28% vanadium pentoxide is leached at 75°C for 180 minutes with a mixed solution of sulfuric acid and HF at a liquid-solid ratio of 4 to 1. The total acidity of concentrated sulfuric acid and hydrofluoric acid is 12 mol / L, and the ratio of the amount of sulfuric acid to hydrofluoric acid is 1 to 1. The leaching rate of titanium is 97.34%, the leaching rate of iron is 98.63%, the leaching rate of aluminum oxide is 96.38%, the leaching rate of vanadium pentoxide is 96.32%, the leaching rate of manganese oxide is greater than 99.9%, and the leaching rate of silicon is 94.33%. Using this leaching solution as a raw material, titanium, iron, aluminum, silicon and other elements are separated.
[0023] The above-mentioned leachate is extracted using C8H17-CO-CH2-CO--C8H17 dissolved in isoamyl ether, with an extractant volume concentration of 45%, an extraction temperature of 50°C, and a ratio of 3:1; after 15 levels of countercurrent extraction, the extraction rates of elements such as titanium, iron, chromium, aluminum and silicon are 98.25%, 98.48%, 27.49%, 66.72% and 98.82% respectively. The obtained organic phase containing titanium, iron, chromium, aluminum and silicon is counter-currently washed for six stages with a solution having a titanium concentration of 40g / L and a hydrogen fluoride concentration of 1.0mol / L at a ratio of 15:1, and the elution rate of chromium is 98.97%; then, it is counter-currently washed for five stages with a solution having an iron concentration of 50g / L and a hydrogen fluoride concentration of 3mol / L, and the elution rate of aluminum is 99.64%; then, it is counter-currently washed for six stages with a 0.5mol / L hydrogen fluoride solution at a ratio of 4:1, and the elution rate of titanium is 98.66%; then, it is counter-currently washed for 10 stages with pure water at a ratio of 2:1, and the washing rate of iron reaches 99.43%; finally, the organic phase is washed with 1.0mol / L sodium hydroxide at a ratio of 15:1, and the number of stages is 10, and the elution rate of silicon is 99.78%. Each washing liquid is concentrated and crystallized to obtain a complex containing fluoride or fluorine. The organic phase is washed with water and returned to the extraction for continued use.
[0024] Example 4
[0025] The titanium-containing raw material containing 23.25% titanium dioxide, 8.01% magnesium oxide, 13.31% aluminum oxide, 25.05% silicon dioxide, 26.94% calcium oxide, and 0.28% vanadium pentoxide is leached at 75°C for 180 minutes with a mixed solution of sulfuric acid and HF at a liquid-solid ratio of 5 to 1. The total acidity of concentrated sulfuric acid and hydrofluoric acid is 12 mol / L, and the ratio of the amount of sulfuric acid to hydrofluoric acid is 1 to 1. The leaching rate of titanium is 98.46%, the leaching rate of iron is 99.71%, the leaching rate of aluminum oxide is 98.49%, the leaching rate of vanadium pentoxide is 97.45%, the leaching rate of manganese oxide is greater than 99.9%, and the leaching rate of silicon is 97.58%. Using this leachate as a raw material, titanium, iron, aluminum, silicon and other elements are separated.
[0026] The above leaching solution uses C8H dissolved in 1-octadecene 17 -CO-CH2-CH2-CO-C8H 17The extraction was carried out with an extractant volume concentration of 38%, an extraction temperature of 50°C, and a ratio of 3.5:1; after 20 levels of countercurrent extraction, the extraction rates of elements such as titanium, iron, chromium, aluminum and silicon were 97.35%, 99.82%, 6.30%, 33.57% and 97.92% respectively. The obtained organic phase containing titanium, iron, chromium, aluminum and silicon is counter-washed for 3 levels with a solution having a titanium concentration of 25g / L and a hydrogen fluoride concentration of 2.0mol / L at a ratio of 15:1, and the elution rate of chromium is 99.73%; then, it is counter-washed for 5 levels with a solution having an iron concentration of 55g / L and a hydrogen fluoride concentration of 2mol / L at a ratio of 3:1, and the elution rate of aluminum is 98.38%; then, the organic phase is counter-washed for 6 levels with a 0.5mol / L hydrogen fluoride solution at a ratio of 3:1, and the elution rate of titanium is 99.49%; then, the organic phase is counter-washed for 8 levels with pure water at a ratio of 1.5:1, and the washing rate of iron reaches 99.56%; finally, the organic phase is washed with 1.0mol / L sodium hydroxide at a ratio of 15:1, the number of levels is 10, and the elution rate of silicon is 99.65%. Each washing solution is concentrated and crystallized to obtain a complex containing fluoride or fluorine. The organic phase is washed with water and returned to the extraction for continued use.
[0027] Comparative Example 1
[0028] The titanium-containing raw material containing 63.44% titanium dioxide, 10.75% total iron, 0.26% sodium oxide, 3.13% magnesium oxide, 4.85% aluminum oxide, 8.96% silicon dioxide, 3.23% calcium oxide, 0.60% vanadium pentoxide, 1.24% chromium trioxide, and 1.52% manganese oxide was leached for 100 minutes at 70°C with a sulfuric acid solution at a liquid-solid ratio of 6 to 1. The acidity of concentrated sulfuric acid is 8 mol / L, the leaching rate of titanium is 65.43%, the leaching rate of iron is 88.15%, the leaching rate of aluminum oxide is 72.33%, the leaching rate of vanadium pentoxide is 88.26%, the leaching rate of manganese oxide is greater than 79.3%, and the leaching rate of silicon is 15.21%. When leaching is only carried out with sulfuric acid, the leaching rate of each element in the titanium-containing raw material is low and the leaching is incomplete.
[0029] Comparative Example 2
[0030] The titanium-containing raw material containing 23.25% titanium dioxide, 8.01% magnesium oxide, 13.31% aluminum oxide, 25.05% silicon dioxide, 26.94% calcium oxide, and 0.28% vanadium pentoxide was leached at 75°C for 180 minutes with a concentrated hydrochloric acid mixed solution at a liquid-solid ratio of 4 to 1. The initial acidity of the hydrochloric acid solution was 12 mol / L. The leaching rate of titanium was 35.73%, the leaching rate of iron was 78.98%, the leaching rate of aluminum oxide was 32.15%, the leaching rate of vanadium pentoxide was 72.64%, the leaching rate of manganese oxide was 23.92%, and the leaching rate of silicon was 5.02%. Compared with mixed acid leaching, the leaching of hydrochloric acid solution was incomplete.
[0031] Comparative Example 3
[0032] The leaching solution of Example 1 was prepared by using C dissolved in dodecylbenzene. 10 H 21 -CO-NH-OH was used for extraction, the volume concentration of the extractant was 30%, the extraction temperature was 45℃, and the ratio was 2.5:1; after 8 levels of countercurrent extraction, the extraction rates of titanium, iron, chromium, aluminum and silicon were 99.32%, 99.92%, 2.5%, 23.24% and 99.88% respectively. The obtained organic phase containing titanium, iron, chromium, aluminum and silicon was countercurrently washed once with a solution having a hydrochloric acid concentration of 6 mol / L at a ratio of 8:1, and the elution rate of chromium was 67.23%. It was then countercurrently washed once with a solution having an iron concentration of 42 g / L and a hydrochloric acid concentration of 6 mol / L, and the elution rate of chromium was 22.53% (relative to the initial concentration of chromium in the organic phase); the elution rate of aluminum was 62.65%, and the obtained washing liquid contained chromium and aluminum, and the separation of chromium and aluminum was not achieved; the organic phase was countercurrently washed once with a 1 mol / L hydrochloric acid solution at a ratio of 2:1, and the elution rate of titanium was 88.69%, and the obtained washing liquid contained chromium, aluminum and titanium. The organic phase was then washed with pure water at a ratio of 1:1, level 1 countercurrent, and the iron washing rate reached 55.86%. The resulting solution contained chromium, aluminum, titanium and iron. Finally, the organic phase was washed with 1.0 mol / L sodium hydroxide, at a ratio of 6:1, level 1, and the silicon elution rate was 59.68%. Severe emulsification occurred, making it impossible to achieve industrial application.
[0033] Therefore, the present application provides a method for comprehensive utilization of multi-metal ilmenite, which solves the technical problem that various elements cannot be comprehensively utilized in the prior art.
[0034] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.
[0035] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for comprehensive utilization of multi-metal ilmenite, characterized in that: The following steps are involved: Step 1: leaching the titanium-containing raw material with a mixed acid to obtain a leaching solution; Step 2: dissolving the leachate in a mixed solution of an extractant and an organic solvent for countercurrent extraction, and countercurrently washing the obtained organic phase containing titanium, iron, chromium, aluminum and silicon with a mixed solution of titanium ions and hydrogen fluoride, and then countercurrently washing with a mixed solution of iron ions and hydrogen fluoride solution, and then countercurrently washing the organic phase with a hydrogen fluoride solution, and then countercurrently washing the organic phase with pure water, and finally washing the organic phase with sodium hydroxide or sodium carbonate.
2. The comprehensive utilization method of multi-metal ilmenite according to claim 1, characterized in that: In step 1, the mixed acid is sulfuric acid and hydrochloric acid, or sulfuric acid and chlorides such as sodium chloride and magnesium chloride, or the mixed acid is sulfuric acid and HF, or sulfuric acid and fluorides such as sodium fluoride and ammonium fluoride, a binary mixed acid system; or a ternary mixed acid system such as sulfuric acid containing chlorine and fluoride ions.
3. The comprehensive utilization method of multi-metal ilmenite according to claim 1, characterized in that: In step 1, the titanium-containing raw material is leached with a mixed acid at a liquid-to-solid ratio of 0.1-10:1 at 10-90°C.
4. The comprehensive utilization method of multi-metal ilmenite according to claim 1, characterized in that: In step 2, the substituents R1 and R2 in the extractant are saturated or unsaturated straight chain or branched alkyl substituents with 1-20 carbon atoms; or saturated or unsaturated straight chain or branched alkyl substituted phenyl with 1-20 carbon atoms; or primary or secondary amine groups substituted with saturated or unsaturated straight chain or branched alkyl groups with 1-20 carbon atoms.
5. The comprehensive utilization method of multi-metal ilmenite according to claim 1, characterized in that: In step 2, the organic solvent is dissolved in a saturated or unsaturated straight or branched alkane with a carbon number of 6-20; or a saturated or unsaturated straight or branched alkyl substituted benzene with a carbon number of 6-20; or an ether substituted with a saturated or unsaturated straight or branched alkyl with a carbon number of 6-20.
6. The comprehensive utilization method of multi-metal ilmenite according to claim 1, characterized in that: In step 2, the concentration of chlorine or fluorine ions ranges from 0.1-12 mol / L, the concentration of iron or titanium ions ranges from 0.1-60 g / L, and the washing ratio of the mixed solution is 0.1-25 to 1, and the washing temperature is 10-80°C.
7. The comprehensive utilization method of multi-metal ilmenite according to claim 1, characterized in that: The concentration range of sodium hydroxide or sodium carbonate detergent is 0-12 mol / L, the washing ratio is 0.1-25 to 1, and the washing temperature is 10-80°C.
Citation Information
Patent Citations
Method for selectively leaching titanium from titaniferous slag
CN110453093A
Method for microwave alkali roasting of titanium concentrate and ultrasonic sulfuric acid leaching of titanium
CN116287784A
Process for preparing artificial rutile by leaching ilmenite with hydrochloric acid
CN117800389A
Method for preparing titanium dioxide by using titanium-rich material
CN117865217A
Clean production method for preparing rutile titanium dioxide from ilmenite
CN101531397A